Pengembangan LKS Berbasis Kearifan Lokal (Motif Batik Durian) pada Mata Pelajaran IPS Kelas V - Nuriyah, Dewi; Prananosa, Ahmad Gawdy; Rosalina, Elya (IJOCE: Indonesia Journal of Civic Education, 2024)
This study aims to produce a valid, practical, and effective local wisdom-based Student Worksheet (durian batik motif) in social studies subjects. This research is a development research using the 4D model. In this model there are 4 stages, namely 1) define (definition stage) 2) design (design stage) 3) develop (development stage), and 4) disseminate (dissemination stage). The subjects of this study included 3 validators (linguists, material experts, and media) as well as class teachers, VB class students in the teacher and student practicality test (small group and large group test). The data collection technique was carried out using a Likert scale questionnaire and for the large group trial a learning outcome test. Based on the results of the validation questionnaire assessment analysis carried out by the validators, it showed that the Student Worksheet that had been developed met the criteria of being very valid with a product validity score of 0.85. Meanwhile, the results of the analysis of the practicality questionnaire assessment conducted by teachers and students showed that the LKS that had been developed met the criteria of being very practical with a product practicality score of 4.75 with a maximum score of 5. Then the results of the effectiveness analysis that had been carried out with student learning outcome tests showed that the LKS met the very good category with a classical completion score of 87%. So based on these data, it can be concluded that the LKS that had been developed in this study were declared very valid, very practical, and very good so that they could be used in learning social studies subjects. Keywords: Social Studies, LKS, Development, 4D